2008
DOI: 10.1002/smll.200700456
|View full text |Cite
|
Sign up to set email alerts
|

Simple Synthesis of Functionalized Superparamagnetic Magnetite/Silica Core/Shell Nanoparticles and their Application as Magnetically Separable High‐Performance Biocatalysts

Abstract: Uniformly sized silica-coated magnetic nanoparticles (magnetite@silica) are synthesized in a simple one-pot process using reverse micelles as nanoreactors. The core diameter of the magnetic nanoparticles is easily controlled by adjusting the w value ([polar solvent]/[surfactant]) in the reverse-micelle solution, and the thickness of the silica shell is easily controlled by varying the amount of tetraethyl orthosilicate added after the synthesis of the magnetite cores. Several grams of monodisperse magnetite@si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
163
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 356 publications
(176 citation statements)
references
References 48 publications
(11 reference statements)
5
163
0
4
Order By: Relevance
“…Moreover, NPs size is dependent on the constant rates of hydrolysis and condensation steps as a function of the reaction mixture (33). Similar to earlier works (17,(34)(35), we demonstrated that silica shell thickness around magnetite nanoparticles will increase with increasing the TEOS amount and the size of silica NPs. The latter itself is being increased by increasing the concentration of the precursor.…”
Section: Nps Synthesizesupporting
confidence: 88%
“…Moreover, NPs size is dependent on the constant rates of hydrolysis and condensation steps as a function of the reaction mixture (33). Similar to earlier works (17,(34)(35), we demonstrated that silica shell thickness around magnetite nanoparticles will increase with increasing the TEOS amount and the size of silica NPs. The latter itself is being increased by increasing the concentration of the precursor.…”
Section: Nps Synthesizesupporting
confidence: 88%
“…The thickness of the silica shell, on the other hand, can be controlled by the TEOS concentration. [ 53,54 ] We also studied the effects of MNP-C, TEOS, and NH 4 OH concentrations on the sol-gel reactions. Under the conditions shown in Table S1, row 1, discrete, uniform nanoparticles are formed in MFSNP-1 ( Figure S3).…”
Section: Reaction Optimizationmentioning
confidence: 99%
“…The synergetic effects between the core and shell materials may drastically improve the overall performance of the hybrid composites, which results in a range of potential applications, including biomedical application [3,4], catalysis [5,6], electronics [7] and chemical sensors [8]. The properties of core-shell nanostructures can be adjusted by changing either the constituting materials or the core to shell ratio [9].…”
Section: Introductionmentioning
confidence: 99%